Minimizing Interference in Robotic Rehabilitation via Asymmetric Stiffness Force Fields - Yasuhiro Kato; Sho Sakaino; Toshiaki Tsuji (IEEE Open Journal of the Industrial Electronics Society)
This article introduces a novel approach for guiding human arm movement in the context of robotic rehabilitation. We propose upper limb movement guidance using a force field based on an asymmetric stiffness matrix. By introducing asymmetry in stiffness design, the proposed force field can deflect arm movement toward the target direction of a reaching movement while minimizing impeding effects. We hypothesize that this method can guide a human in the desired direction without interfering with their voluntary movement. To evaluate the performance of the human arm guidance technique, we conducted upper limb reaching experiments using a 2-degree-of-freedom robot arm with ten healthy volunteers. The experimental results revealed that the proposed approach demonstrated a similar reduction in movement error compared to the conventional stiffness approach. Moreover, participants exhibited higher movement activeness, and robotic interference with human movement was lower. The proposed approach may improve movement guidance based on stiffness control by enabling the robot to guide without inhibiting voluntary movement.